A New Commentary on Virgil, AENEID Book 8 - Tarrant, Richard (Exemplaria Classica, 2019)
Lee M. Fratantuono– R. AldenSmith, Virgil, Aeneid 8; Text, Translation, and Commentary. Mnemosyne, Supplements, 416. Leiden: Brill, 2018, 802 pp., ISBN: 978-90-04- 36735-7.